PENGARUH DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH, KABUPATEN JAYAPURA, PAPUA - Rohimah Handayani Sri Lestari; Fransiskus Palobo (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
Shallots is one of the important commodities in Indonesia. Demand for these commodities always increases along with population growth. To fulfill this demand, the production of shallots must always be increased. One way to increase the production of shallots is by fertilizing. This study aims to determine the dosage of NPK fertilizer which gives the best results for the growth and yield of shallots. The study was carried out in Sentani District, Papua Province, from November 2016 until March 2017.The study used the Randomized Complete Block Design (RCBD) with three treatments NPK Phonska fertilization (NPK 15-15-15 composition) and four repplication. NPK fertilizer used were: 1) NPK 300 kg/ha, 2) 250 kg/ha, and 3) 200 kg/ha. The meterials used were shaloot bulbs Keta Monca cultivar. The plot size was 1 x 5 m, with a spacing of 15 x 15 cm. NPK fertilizer was given at the age of 14 and 30 days after planting respectively with the dose of ½. The variables observed were plant height, leaf number, bulbs number per sample, diameter of bulbs, dry weight bulb per hectare The results showed that the treatment of NPK fertilizer dosage did not give a significant effect on almost all observation variables except on the dry weight of eskip bulb, where the treatment dose of 200 kg/ha NPK fertilizer gave the highest yield compared to other treatments. When observed from the growth components and production components, the dose of NPK fertilizer 200 kg/ha is the most consistent to provide better growth and yield.